Efeitos da interdependência social e orientação de valor social sobre a formação de folga orçamentária - Gazso, Maria Carolina Oliveira (2012)
This paper aims to analyze the effects of the social value orientation and the social interdependence on the Budgetary slack. Budgetary slack is a subject very studied by international researchers as a dysfunctional budget problem, however until now, with no clear conclusion about your causes. Assuming that this subject impacts organization process of planning, results and competitiveness, this paper intend to contribute to budgetary slack knowledge based on social theories of social value and interdependence and slack theory, originated in the economics, most specifically, in the agency theory. It was applied a questionnaire, a budget experiment and an instrument to measure social value orientation among 41 leaders oh Tower International Company. According to statistic analysis, it was not possible to validate the hypothesis of this research, but considering the theories used on that, It is clear that there is a vast potential on the search of best practices in the management accounting area.